(untitled) (GIST – Education and Learning Research Journal, 2018)
This article is about an Action Research project carried out at a public Institution in Sincelejo, Colombia. The research purpose was to determine the effect of transactional communication strategies (TCS) on pre-service teachers’ speaking skill. In a diagnostic stage, problems in the speaking skill were identified then an action stage was carried out consisting of six workshops including TCS; a researcher journal, a student self-assessment survey, and a non-participant observation were used for data collection; results suggested a positive impact of TCS on the participants’ speaking skill represented in significant progress related to vocabulary, grammar, fluency, attitude, pronunciation, and interaction. Conclusions ratify the importance of TCS in the preparation of future Elementary School teachers in response to national bilingualism policies.